2016
DOI: 10.1074/mcp.r115.053330
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegeneration and Alzheimer's disease (AD). What Can Proteomics Tell Us About the Alzheimer's Brain?

Abstract: Neurodegenerative diseases, such as Alzheimers diseases (AD), are becoming more prevalent as the population ages. However, the mechanisms that lead to synapse destabilization and neuron death remain elusive. The advent of proteomics has allowed for high-throughput screening methods to search for biomarkers that could lead to early diagnosis and treatment and to identify alterations in the cellular proteome that could provide insight into disease etiology and possible treatment avenues. In this review, we have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 151 publications
(174 reference statements)
2
71
0
1
Order By: Relevance
“…Furthermore, due to the multifaceted etiopathology of AD, new proteomics research is needed to advance the understanding and diagnostic tools of this disease by looking at the molecular and neurophysiological mechanisms underlying AD [9,174176]. Analysis of biochemical markers that can be used to diagnose the various stages of this disease, as well as elucidation of neurobiological changes that occur throughout AD, are vital to advancing this field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, due to the multifaceted etiopathology of AD, new proteomics research is needed to advance the understanding and diagnostic tools of this disease by looking at the molecular and neurophysiological mechanisms underlying AD [9,174176]. Analysis of biochemical markers that can be used to diagnose the various stages of this disease, as well as elucidation of neurobiological changes that occur throughout AD, are vital to advancing this field.…”
Section: Discussionmentioning
confidence: 99%
“…Neurodegenerative processes that contribute to atrophy and memory decline occur in specific brain areas like the neocortex and limbic system and are characterized by synaptic damage and neuronal death, with these changes corresponding to the classical cognitive impairment and memory loss associated with AD [9,106110]. In experiments looking at multiple sclerosis (MS), an inflammatory disease characterized by extensive demyelination, it has been found that neuroinflammation has detrimental effects on synaptic transmission, particularly in the hippocampus, further elucidating the hippocampal cognitive deficits and attenuation of synaptic plasticity that result in pathologies due to CNS inflammation [111,112].…”
Section: Neurodegenerative Pathology and Neuroinflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Supported by the correlation of AD symptoms with downregulation of L-PGDS concentration in the CSF of AD brain, we posit that L-PGDS targets Aβ in AD mouse brain with high turnover suggestive of fast kinetic binding [10][11][12]. Therefore, we reason that L-PGDS expressed in other brain regions takes part in other biological functions and can play a more active neuroprotective role.…”
Section: Introductionmentioning
confidence: 78%
“…In this case, a proteomics study of normal synaptic functions provides insights on new roles for neurodegeneration-associated proteins. Synapse dysfunction and loss are implicated in neurodegenerative diseases and the review of Moya-Alvarado et al (11) summarizes progress in applying proteomics to the pathophysiology and diagnosis of Alzheimer's disease. Links to neurological diseases are also seen in primary research papers in this issue.…”
mentioning
confidence: 99%